2009
DOI: 10.1149/1.3160549
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Thermally Robust 5 nm Ru–C Diffusion Barrier/Cu Seed Layer in Cu Metallization

Abstract: Sputtered Ru and Ru-C films 5 nm thick are employed in the Cu/barrier/SiO 2 /Si system, and their performances as the diffusion barrier as well as the seed layer for direct Cu electroplating are investigated in parallel. Based on the sheet resistance measurement and energy dispersive X-ray line profiles, the 5 nm Ru-C film can retard the diffusion of Cu after a prolonged ͑30 min͒ annealing up to 700°C, while the Ru film is an effective barrier up to only 400°C. Direct electroplating of Cu is successfully carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Redistribution subject to ECS terms of use (see 138.251.14. 35 Downloaded on 2015-03-14 to IP majority of the inner film of both the as-deposited and annealed film is composed of metallic Cu. It has been reported that Ar + sputtering can reduce oxide to its metallic form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Redistribution subject to ECS terms of use (see 138.251.14. 35 Downloaded on 2015-03-14 to IP majority of the inner film of both the as-deposited and annealed film is composed of metallic Cu. It has been reported that Ar + sputtering can reduce oxide to its metallic form.…”
Section: Resultsmentioning
confidence: 99%
“…ecsdl.org/site/terms_use address. Redistribution subject to ECS terms of use (see 138.251.14 35. Downloaded on 2015-03-14 to IP…”
mentioning
confidence: 99%
“…[3,5,14]) between Cu and SiO 2 or Si, the sharp increase in sheet resistance of the 700 • C annealed sample cannot be attributed to the interdiffusions and reactions in the Cu/Ni-Al-N/SiO 2 /Si heterostructure. Very recently, it was reported that agglomeration of Cu could occur due to the internal stress of Cu film itself and thermal stress of interface between Cu and its underlayer [14,15]. In this case, holes and hills exist in Cu film so that Cu film is no longer continuous, leading to a strong electron scattering and thus increasing noticeably the sheet resistance of the samples.To further confirm the failure mechanism of Ni-Al-N barrier, surface morphologies of the Cu/Ni-Al-N/SiO 2 /Si heterostructures annealed at various temperatures from 500 to 700 • C were investigated using an atomic force microscope.…”
Section: Resultsmentioning
confidence: 99%
“…Ru has drawn much attention lately as adhesion layer and possible diffusion barrier for Cu interconnects in VLSI circuits. While the diffusion barrier properties of sputtered Ru layers are less attractive, wetting and adhesion experiments have shown promising results [5][6][7][8]. In all cases presented here, except if noted elsewise, a thin Ti layer is deposited prior to the diffusion barrier to imitate the Ti or Ti-Si contacts to the active device areas.…”
Section: Introductionmentioning
confidence: 91%